Persepsi Siswa Terhadap Mata Pelajaran IPA Pada Jurusan Bisnis Dan Manajemen SMK Negeri 2 Dan SMK Negeri 3 Kota Padang - Fitrianti, Rita; Risdawati, Renny; Paas Megahati, Ruth Rize (Pendidikan Biologi, 2013)
ABSTRACTThis research was aimed at revealing the perception of the vocational schoolstudents toward Natural Science subject. This was a descriptive research. The population of the research was the students in class X of SMKN  (SMKN 2 and SMKN 3) majoring in Business and Management registered in the second semester of January-June 2013. The number of the population was 94 students; 48 students of SMKN 2 Padang   and 46 students of SMKN 3 Padang. Through simple random sampling technique, 20% of the population was taken as the sample. The data was gathered by using questionnaires of Likert  scale.  It  then  was  analyzed  by  using  percentage  formula  whose  result  was confirmed qualitatively into 5 category; very good, good, adequate, less adequate and poor. The result of the research indicated that the perception of the students majoring in Business and Management in SMKN 2 Padang and SMKN 3 Padang toward Natural Science subject was good (75,15%).